A comparison of methods for assessing preference for social interactions. Issue 2 (5th March 2020) - Morris, Samuel L.; Vollmer, Timothy R.
Abstract : Researchers have evaluated a variety of methods for assessing preference for social interactions, and generally have found that such assessments accurately identify differentially reinforcing, preferred interactions. However, few researchers have compared methods for assessing preference for social interactions, and none have done so with participants across different skill levels. The current study compared the stability and validity of hierarchies produced by social interaction preference assessments (SIPA) and picture‐based multiple stimulus without replacement preference assessments (MSWO) with 8 individuals diagnosed with autism spectrum disorder (ASD). The MSWO most often produced valid hierarchies for participants who could match, identify, and tact pictures of social interactions and that the SIPA most often produced valid hierarchies for participants who could not identify or tact pictures of social interactions. A vocal paired‐stimulus preference assessment (PSPA) was also conducted with a subset of participants who communicated vocally, and it produced valid hierarchies. Considerations and recommendations for selecting a method of assessing preference for social interactions are discussed.